Competency Level of Secondary School Administrators and Their Administrative Performance: Basis for a Training Program in School Management - Cañete, Esmole (IJRDO- Journal of Educational Research, 2020)
This study sought to identify the competency level of secondary School Administrators and their administrative performance which a basis for a training program in school management. There were 10 districts included in this study under the Division of Bayawan City. The total number of respondents consisted of 26 school administrators and 260 teachers. The study was a combination of descriptive and correlational research. The statistical tools used were percentage, mean μ, weighted mean μ and Pearson Product-Moment Correlation Coefficient. The study revealed that majority of the school heads’ performance evaluation coming from their Key Result areas (KRA) were very satisfactory. The study also found out that there is a significant relationship between the school administrators’ competency level (in all areas) and their performance based on RPMS. The data also reflect that all the values of r are classified to be in the moderate category.